Recurrent Acute Disseminated Encephalomyelitis (ADEM) after COVID-19-vaccination and after subsequent COVID-19-infection: A case report (part II) - Poli, Khouloud; Kowarik, Markus; Hamprecht, Klaus; Iftner, Thomas; Ernemann, Ulrike; Ziemann, Ulf; Poli, Sven (Frontiers in Neurology, 2023)
Acute disseminated encephalomyelitis (ADEM) is an autoimmune disorder of the central nervous system (CNS), which is commonly associated to previous viral infection or immunization. Cases of ADEM with a potential relationship to both severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and vaccination have been reported. We recently published a rare case of a 65-year-old patient who suffered from a corticosteroid- and immunoglobulin-refractory multiple autoimmune syndrome including ADEM following Pfizer-BioNTech coronavirus disease (COVID)-19 vaccination, and whose symptoms largely resolved after repeated plasma exchange (PE). Four months later, the patient was diagnosed with SARS-CoV-2 omicron variant infection after experiencing mild upper respiratory tract symptoms. Few days later, the patient developed severe tetraparesis with magnetic resonance imaging (MRI) showing multiple new inflammatory contrast-enhancing lesions in the left middle cerebellar peduncle, cervical spinal cord, and ventral conus medullaris. Repeated cerebrospinal fluid (CSF) analyses indicated blood-brain barrier damage (increased albumin ratio) without signs of SARS-CoV-2 invasion (mild pleocytosis, no intrathecal antibody production). SARS-CoV-2 specific immunoglobulin G (IgG) were detected in serum and to a much lower degree in CSF with close correlation between both concentrations over time, reflecting antibody dynamics of vaccine- and infection-induced immune response, and blood-brain barrier patency. Daily PE therapy was initiated. Given the patient's lack of improvement after seven PE, treatment with rituximab was considered. After a first dose, however, the patient suffered epididymo-orchitis leading to sepsis, and declined rituximab continuation. At 3-months follow-up, clinical symptoms had dramatically improved. The patient regained walking ability without assistance. This case of recurrent ADEM after COVID-19-vaccination and after subsequent COVID-19-infection strongly supports the hypotheses of neuroimmunological complications in these conditions being promoted by a systemic immune response and mediated by molecular mimicry of, both, viral and vaccine SARS-CoV-2 antigens and CNS self-antigens.